A novel tissue-selective β2-adrenoceptor agonist with minimized cardiovascular effects, 5-HOB, attenuates neuropathic pain in mice - Marie Jourdain; Shinji Hatakeyama (BMC Research Notes, 2019)
Abstract Objective 5-HOB is a novel tissue selective, 5-hydroxybenzothiazolone-derived β2 adrenoceptor agonist with minimized cardiovascular effects while retaining efficacy on skeletal muscle in preclinical experiments unlike conventional β2 adrenoceptor agonists, however its effect on the nervous system has not been evaluated yet. Therefore, 5-HOB was evaluated in a mouse model of neuropathic pain. Results 5-HOB alleviated neuropathic allodynia in a dose dependent manner and reversed the changes in hind paw withdrawal thresholds to the sham control levels. The dose attenuating neuropathic allodynia was slightly lower than the dose inducing skeletal muscle hypertrophy. In conclusion, as reported with known β2 adrenoceptor agonists, 5-HOB was also effective in attenuating neuropathic pain in mice in addition to its effect on skeletal muscle.